Importance of applying operational methodological techniques during the period of teaching - learning English in University undergraduate - Veliz Blacio, Jacqueline Jeaneen (RECIMUNDO, 2020)
Learning in university education must guarantee that students learn to study and research, to enhance the desire to know more and better every day. It must train competent professionals, develop them integrally in different orders: intellectual, social, ethical, aesthetic, political-ideological. The English subject is developed through the following general methods and techniques, in many universities: master class, individual work, debates, reading on related web pages, personalized tutorials, exercises and practical activities. The new English language strategy in higher education is aimed at achieving a culture of training in foreign languages by students and teachers. It contemplates the implementation of didactic methods and procedures typical of a teaching-learning. The use of technology can improve quality and offer a short-term solution to the lack of teachers with high levels of English proficiency. Some tools that facilitate learning: Skype, forums, blogs, YouTube, among others. Therefore, it is relevant to mention that ICT constitutes an instrument to help teaching staff to plan and develop their lessons. No doubt, the integration of ICTs also implies costs and problems, but the change is absolutely essential, since we are in a new era in which ICTs are a powerful and versatile instrument that allow the development of new skills and forms of knowledge construction. A descriptive methodology was applied.